PERANCANGAN SISTEM INFORMASI MANAJEMEN ASET DAN INVENTARIS SMK N 7 PADANG - Fitra Sani; Dharma Liza Said; Denny Kurniadi (Universitas Negeri Padang, 2014)
Processing of asset management and inventarize at SMKN 7 Padang running manually such as inventarize of new stuff to be record through ledger by hand. Cause of that, the managing asset operator have troubles to manage and making asset management reports, managing and checking supply data of stuff, list of entry and ordering stuff, difficult to search data and making data stuff that already exist. To solve this problem, we made an information management system of asset management and inventaries. Scheme of the system method used system development life cycle (SDLC). It start from system design to phase scheme of detailed system, like flowmap, and DBMS (Database Of Management System) for databases, normalization, ERD (Entity Relationship diagram) and also use Java for language program and Neatbeans 7.4 for IDE. It will be implemented through the desktop. The advantages of this application is : facilitating in data processing and help the operator to manage the asset of inventaries at SMKN 7 Padang. Beside that, this program provide simplicity for students, teachers, and visitors to borrowing and repayment asset of inventarize at SMKN 7 Padang.